Using 2-colorings in the theory of uniquely Hamiltonian graphs - Zeps, Dainis (My University, 2019)
We use the concept of 2-coloring in analyzing UH3 graphs and building exact specifications of functions to find new UH3 graphs by Hamiltonian cycle edge extractions
Keywords: graph theory, uniquely Hamiltonian graphs, Thomassen's conjecture